The lying room - French, Nicci (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2019)
A married woman's affair with her boss spirals into a dangerous game of chess with the police when she discovers he's been murdered and she clears the crime scene of all evidence. One little secret between a married woman, her lover, and a killer..."--provided by publisher.
Keywords: Adultery -- Fiction; Murder -- Investigation -- Fiction; Thrillers (Fiction)